61‐1: Invited Paper: Enhanced Viewing Experience Considering Chromatic Adaptation. Issue 1 (29th May 2019) - Wu, Jiaying; Zhang, Lu; Isikman, Serhan; Chen, Cheng
Abstract : We describe the advanced chromatic adaptation model and framework employed in Apple's True Tone Displays. Combining the theoretical model and empirical user study results, True Tone Display is able to deliver a more color consistent viewing experience.